The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.37939/jrmc.v25i1.1563
|View full text |Cite
|
Sign up to set email alerts
|

HRCT Spectrum in Initially COVID-19 RT-PCR Negative Patients

Abstract: Objective: To analyze radiological spectrum of HRCT in COVID-19 patients, clinically symptomatic but initially having negative RT-PCR. Study Design: Prospective cross sectional descriptive study. Place and Duration of Study: Radiology and Medicine Department, DHQ Hospital Rawalpindi, from June to November 2020 Methodology: The study included 90 patients presenting with clinical symptoms of COVID-19 but with negative RT-PCR. All patients underwent chest computed tomography (CT). Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Various researchers had worked on chest X-ray images COVID detection mechanism [21]. Different machine learning and deep learning models had applied for prediction of COVID [22].…”
Section: Comparative Analysis Of Proposed Workmentioning
confidence: 99%
“…Various researchers had worked on chest X-ray images COVID detection mechanism [21]. Different machine learning and deep learning models had applied for prediction of COVID [22].…”
Section: Comparative Analysis Of Proposed Workmentioning
confidence: 99%
“…According to Khatri et al (1999), job hopping definition varies from one country to another, Settersten and Ray (2010) even renamed job hopping as job shopping which refers to the action of those who frequently change jobs, not necessarily due to anxiety or change but deploy as a strategy for better progress and profits. Generally, job hopping occurs for positive purposes, such as seeking for working experience and better rewards (Saleem et al, 2016), quick financial gains or career advancement (Naresh and Rathnam, 2015). Besides that, Yuen (2016) study conducted in Hong Kong has confirmed that job hopping occurs voluntarily and not forcibly (e.g., dismissal).…”
Section: Introductionmentioning
confidence: 99%